Relationship between politics and administration: a comparative analysis of legislation and governance in Pacific Island governmental systems - Ugyel, Lhawang (2017)
The politics-administration dichotomy has long been a subject of considerable debate in public administration. Despite the argument that there is no strict separation between politics and administration, the tension between the two continues to be significant. In response, this article explores why, and the extent to which, countries seek by various legislative means to maintain political neutrality in administration and restrict political involvement by public servants. The focus is on arrangements in 12 Pacific Island governmental systems with the aim of determining whether or not provisions in legislation address important aspects of political neutrality and political involvement and what the implications are for governance. Significantly, the dynamics and complexities in forging an appropriate balance between politics and administration vary considerably from one system to another. On the basis of indicators of government capacity and effectiveness in the Pacific, it is not possible to make causal claims or to discern distinctive patterns in the relationship between politics and administration. - Reproduced.
Keywords: Public administration